The Effect of Education Level and Information Technology Sophistication on the Effective Use of Accounting Information Systems (E-Jurnal Akuntansi, 2026)
Technological developments have a major influence on the accounting information system (AIS) in a company. Technology-based accounting information systems are very helpful for companies that use them, one of which is the Rural Credit Bank. The purpose of this study was to determine the level of education and sophistication of information technology on the effectiveness of using accounting information systems at BPR Denpasar City. The number of samples in this study were 90 samples using a purposive sampling technique. In this study using SPSS for the classical assumption test technique, Model Fit test and Hypothesis test. Based on the results of this study it can be concluded that the level of education has a positive and significant effect on the Effectiveness of Using the AIS. The higher the level of education, the effectiveness of using SIA will also increase and the sophistication of information technology has a positive and significant effect on the effectiveness of using AIS. The higher the sophistication of information technology, the effectiveness of using AIS will also increase. The implications of this research can develop information technology on the use of AIS at BPR Denpasar City.
Keywords: Level of Education; Sophistication of Information Technology; Effectiveness of Using Accounting Information System